2012
DOI: 10.1245/s10434-012-2710-y
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Triple Test for Palpable Breast Masses: The Value of Ultrasound and Core Needle Biopsy

Abstract: For patients with a palpable breast mass and a mTTS score of 3-4, no further assessment is necessary. Those with a mTTS of 8-9 can proceed to definitive therapy. Patients with a mTTS of 5-7 require further assessment. US and/or core biopsy added little to the accuracy or predictive value of the original TTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
25
1
Order By: Relevance
“…In fact, most women presenting with breast alterations will be found to have a benign diagnosis [5]. When first assessing a breast mass, the triple assessment approach to breast lesions is advocated in many countries, which combines clinical, radiologic, and pathologic information to ensure accurate diagnosis and patient management [6, 7]. Traditionally, the triple test consisted of clinical examination, mammography, and FNAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most women presenting with breast alterations will be found to have a benign diagnosis [5]. When first assessing a breast mass, the triple assessment approach to breast lesions is advocated in many countries, which combines clinical, radiologic, and pathologic information to ensure accurate diagnosis and patient management [6, 7]. Traditionally, the triple test consisted of clinical examination, mammography, and FNAB.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the triple test consisted of clinical examination, mammography, and FNAB. Over recent years, the definition has been expanded to include ultrasound in selected age groups (young women) and CNB as an alternative to FNAB cytology [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Even though palpable or non-palpable probably benign lesions have a short-interval imaging follow-up recommended rather than biopsy, the triple test (physical examination, mammogram, and fineneedle aspiration) or modified triple test (physical examination, mammography and/or ultrasonography, and fine-needle aspiration and/or biopsy) has been used to evaluate palpable lesions in clinical practice [5]. However, there is relatively little research on the accuracy of core needle biopsy for palpable lesions [6-9] and, in particular, on its ability to identify borderline lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with physical examination and radiological findings, a diagnostic triad commonly known as the triple test, FNA cytology (FNAC) of palpable breast lesions has been shown to have a sensitivity of 92.7-93.0% and a specificity of 94.8-98.0% for breast carcinoma [1,2]. Although core biopsy has gradually eclipsed breast FNAC in popularity because it offers an improved ability to distinguish invasive from in situ carcinoma and an increased availability of tissue for prognostic studies, large studies have confirmed that FNAC has equivalent accuracy in distinguishing benign from malignant tumors [3,4,5]. Moreover, FNAC has been shown to be more cost-effective than core biopsy for palpable lesions [6] and remains an important diagnostic tool in low-resource settings.…”
Section: Introductionmentioning
confidence: 99%